Android-Based Role-Playing Educational Games to Support Strengthening Children’s Character Education in Elementary School - Muhammad Asrul Sultan; Maryam, Muqinah; Wawan Krismanto (LPPM Undiksha, 2025)
Strengthening character education in elementary school-age children is still largely carried out through conventional learning media, while the rapid development of technology requires teachers to innovate in developing more interesting and relevant media. This research aims to develop and evaluate the feasibility of role-playing educational games designed to support the strengthening of children's character education in elementary schools. This type of research is research and development that refers to the Borg and Gall models, and follows the development stages of role-playing-based games. The subjects in this study were seven grade IV students who were selected based on their experience playing Android-based games. Data was collected through questionnaires designed to assess three aspects, namely aspects of software engineering, visual communication, and learning design. The instruments were validated by media experts, material experts, and classroom teachers. The data analysis technique uses the Likert scale and the calculation of the percentage of media feasibility based on Arikunto's criteria. The results of the study show that the educational game developed has the main characteristics of being compatible with various versions of Android (Marshmallow to Upside Down Cake), file size of 419 MB, running offline, lasting about 1 hour and 30 minutes, and raising the theme of character education and bullying issues through a light and easy-to-understand storyline. The implication is that teachers can use this educational game as an innovative learning medium to instill character values in a more interesting and contextual way for students.